Kemampuan Kecepatan Tendang Mawashi Geri Pada Karateka Dojo Palapa Saiyo (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The speed of the mawashi geri kick is one of the physical components that greatly determines the success of karateka in gaining points during the match, so it is necessary to know the profile of their abilities objectively. This study aims to describe the speed of the mawashi geri kick of karateka Dojo Palapa Saiyo Padang Pariaman as a basis for evaluating the physical condition of athletes. The study used a quantitative descriptive approach with a survey design. The research subjects were 10 karateka selected through a purposive sampling technique based on the criteria of age and class of competition, ranging from early age to junior. Data collection was carried out through a mawashi geri kick speed test which was carried out three repetitions for each athlete, with the measurement results expressed in seconds. Data were analyzed using descriptive statistics to describe the average value, the fastest time, and the slowest time, as well as the categorization of the kick speed level. The results showed that the average karateka kick speed was 2.43 seconds, with the fastest time being 1.34 seconds and the slowest 3.71 seconds. In general, the majority of karateka were in the "sufficient" and "less" categories, which indicates that their explosive power and leg movement speed have not developed optimally. These findings can be a reference for coaches in developing more structured physical training programs that focus on increasing kicking speed.